De la clandestinité à l'affirmation : pour une histoire de la communauté gaie montréalaise - Higgins, Ross (Comeau & Nadeau, 1999)
Survol historique de la communauté gaie-lesbienne de Montréal. D'après l'auteur, ce premier volume sera suivi d'une publication ultérieure où son enquête sera présentée de façon plus globale.
Section: 165, [2] p
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire; histoire et politique; hétérosexisme; identités LGBTQIA2+; justice sociale; militance; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; shm4000; soc2014; systèmes d'oppressions; thématiques

Feminist theorists: Three centuries of women's intellectual traditions - Spender, Dale (Women's Press, 1996)
Feminism was not born in 1968. Yet the work of three centuries of feminist thinkers has been dismissed, distorted or forgotten. Even the names of many of them remain unfamiliar, and few have so much as a mention in history books. Feminist Theorists demonstrates once and for all that we can no longer be content with received ideas about 'progress', which may explain the world for men, but which fail to make sense of the historical experience of women. It shows too that contemporary women have a rich intellectual tradition on which to draw for stimulus, inspiration and enjoyment.
Keywords: approches et analyses; cours; discipline; fem1000; histoire; histoire et politique; justice sociale; mouvements féministes; premier cycle; sciences humaines; thématiques; théories féministes